REPRESENTASI KEKERASAN DALAM FILM “THE RAID: REDEMPTION” - Aditya Mulyana; Feri Ferdinan Alamsyah; Yogaprasta Adi Nugraha (UNIVERSITAS PAKUAN, 2019)
AbstractFilm is one of the mass communication media that has one goal that is to provide entertainment. Indonesian films that have penetrated to air in several countries, namely The Raid: Redemption film. This action genre film shows a lot of violent scenes. Hence this study aims to find out how representations related to violence both verbally and non-verbally in the The Raid: Redemption film. In this study to help find meaning in the The Raid: Redemption, the author uses Roland Barthes semiotics which sees everything with levels of denotation, connotation to myth. The qualitative research method retrieval to find out the purpose of violence and how the life and culture of violence that occurs in the The Raid: Redemption film. This research was conducted in the city of Bogor and Jakarta starting from November 2017 to June 2018. Based on the results of research conducted that the violence displayed in the film The Raid: Redemption shows that someone who has the power allows to commit acts of violence both psychologically and phisically. Violence becomes a solution to all the problems that occur in this film. The language used by someone who commits violence tends to be harsh to demean others. Keywords: Violence, Semiotics, Representation, Film, The Raid: Redemption